How legitimate are urban climate planning processes? A comparative assessment of Accra, Ahmedabad, Bonn and São Paulo - Niklas Wagner; Minal Pathak (Environmental Research Communications)
Urban climate action plans (UCAPs) guide cities in identifying key climate risks and in addressing climate change. Designed to guide urban transformation over decades through near-term and long-term actions reducing emissions and/or adapting to the consequences of climate change, UCAPs are intended to have significant impacts. Despite their significance for urban climate governance, the procedural quality of how UCAPs are created remains under-analysed. By analysing UCAPs of four cities from different regions of the world - Accra (Ghana), Bonn (Germany), São Paulo (Brazil), and Ahmedabad (India) - we unpack the quality of UCAP creation processes in terms of their legitimacy including whether and how key stakeholders were involved in shaping the plan. Drawing on 72 semi-structured interviews with actors involved in the plan-creation process and complemented by document analysis, this study conceptualises UCAP creation phases and assesses its quality using the framework of input, throughput, and output legitimacy. In terms of key actors, this study highlights the crucial role city networks played in designing and funding UCAP creation processes. Significant differences in UCAP legitimacy with regards to levels of co-production, transparency, accessibility, and substantive participation across the case studies are shown. Based on these findings this study provides actionable insights for the creation of legitimate and impactful UCAPs to promote just and equitable urban transformations.